Compliance in the Implementation of Health Protocols During the Covid-19 Pandemic - Arifianto Arifianto; Dwi Nur Aini (GLOBAL HEALTH SCIENCE GROUP, 2023)
Compliance and public awareness in implementing health protocols is still low. There are still many people who are found in crowds, not washing their hands, not wearing masks and not implementing physical distancing. The purpose of this research is to find out whether there is a relationship between motivation and community compliance in the implementation of health protocols during the Covid-19 pandemic at the Patemon Gunungpati Semarang exit. This type of research is quantitative with a cross sectional approach. The research location is in the residents of RW 3 and RW 7, Patemon Village, with a sample of 60 respondents. Data were analyzed using Chi Square statistical test. The results showed that the p value of 0.005 was smaller than 0.05. There is a relationship between motivation and community compliance in implementing health protocols during the Covid-19 pandemic at Patemon Exit, Gunungpati District.